PENGGUNAAN KOMIK PADA MATA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Arsy Putri; Rahmi Seri Hanida; Novebri (EDU RESEARCH, 2024)
The research aimed to determine the effect of using comics on class IV science subjects at MI Model Panyabungan. The experimental method yielded the desired results. The resulThe post-test results showed an average value of 79.63 for students in class IVA (control class), and an average value of 81.43 for students in class IVB (experimental class), indicating improved and increased The paired sample t-test yielded the sig value. The 2-tailed t-test resulted in a sig value of 0.360 > 0.05, indicating that if the sig value exceeds 0.05, we accept Ho and reject Ha. This implies that the use of comic media does not impact or enhance the performance of students in class IV MI Panyabungan Model.